Information and Asignification - Gary Genosko (Footprint)
This paper presents a detailed explication of the main tenets of Félix Guattari’s theorisation of asignifying semiotics in the context of the mixed semiotics that he developed in the 1970s and which extended throughout his career. This foundational work on the relationship between asignification and signifying semiologies, and the micropolitical necessity of escaping from meaning in the broadest sense encompassing individuation, double articulation, and limited subjectivation, is contextualised in terms of information theory, in the work of Claude Shannon and Warren Weaver, as well in terms of Roland Barthes’ semiology and suggestive extra-structural conception of signifiers without signifieds or obtuse meaning. Guattari’s favourite examples of asignifying technomaterial info-networks and mushrooms sprouting on manure are both discussed.